BUSINESS DIGITALIZATION AND SME PERFORMANCE IN EMERGING MARKETS: A PLS-SEM ANALYSIS AND SHARIA PERSPECTIVE FROM SOUTHEAST SULAWESI, INDONESIA - Ummi Kalsum; Adzil Arsyi Sabana; Miswar Rohansyah (Referensi Islamika: Jurnal Studi Islam, 2025)
This study examines the impact of business digitalization on Small and Medium Enterprise (SME) performance in Southeast Sulawesi, Indonesia, while investigating the mediating roles of SME characteristics and owner-manager attributes. It also incorporates a sharia economic perspective by exploring how halal compliance, ethical business practices, and Islamic value-based governance support sustainable SME performance within the regional Islamic economic ecosystem. Employing a mixed-methods sequential explanatory design, this research collected quantitative data from 387 SME owner-managers through stratified random sampling across 17 districts/cities in Southeast Sulawesi. Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4.0 analyzed the hypothesized relationships. Qualitative data from 24 in-depth interviews and focus group discussions with 6 groups (8–10 participants each) enriched the quantitative findings, including insights into the adoption of halal practices and sharia-based business principles. Results reveal that business digitalization significantly and positively affects SME performance (β = 0.489, t = 9.847, p < 0.001). Owner-manager characteristics demonstrate substantial direct effects on digitalization (β = 0.412, t = 8.234, p < 0.001), while SME characteristics show moderate effects (β = 0.287, t = 5.642, p < 0.001). The external environment partially moderates the digitalization-performance relationship (β = 0.156, t = 3.127, p < 0.01). The model explains 52.4% of the variance in SME performance (R² = 0.524) with strong predictive relevance (Q² = 0.387). From a sharia perspective, SMEs that integrate halal certification, ethical compliance, and trust-based transactions tend to demonstrate stronger performance and market acceptance. This study contributes to the limited literature on SME digitalization in Indonesian emerging markets by providing empirical evidence through rigorous PLS-SEM analysis. The integration of Actor-Network Theory with technology adoption frameworks offers a novel theoretical lens for understanding digitalization dynamics in resource-constrained contexts. Furthermore, by embedding Islamic economic principles, this study highlights the role of sharia compliance in enhancing SME competitiveness, supporting the development of a sustainable and inclusive halal economic ecosystem.